Strategic Human Resource Management in Transforming Multicultural Pedagogical Competence: A Case Study of Islamic International Boarding School. - Dwi Fitri Wiyono; Pg Siti Katijah Pg Sulaiman; Dian Mohammad Hakim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyse the implementation of Strategic Human Resource Management (SHRM) in transforming multicultural pedagogical competencies at Thursina International Islamic Boarding School in Malang, Indonesia. It explores how aligning institutional vision, organisational culture, and human resources fosters multicultural and transformative pedagogy within an Islamic educational institution. This study employs a qualitative approach using a single-case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and pupils. The validity of the data was strengthened through triangulation of sources and methods. The findings of this study indicate that SHRM is systematically implemented through diversity-based recruitment, continuous professional development, an organisational learning culture, and the integration of religious, caring, open-minded, and inspiring values into pedagogical practices and institutional culture. Educators are positioned as multicultural mentors who integrate professionalism, spirituality, and cross-cultural sensitivity into the learning process. This study has produced the Prophetic Strategic Human Resource Management (P-SHRM) model, which integrates modern SHRM with Islamic prophetic values such as sincerity, trustworthiness, zeal, and mercy to all creation. This study makes a theoretical contribution to the development of the SHRM literature in multicultural Islamic education by positioning human resource management not merely as a strategy for enhancing organisational performance but as a mechanism for ethical, spiritual, and multicultural transformation within Islamic educational institutions.